The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmj.m2397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food supplementation on cognitive function, cerebral blood flow, and nutritional status in young children at risk of undernutrition: randomized controlled trial

Abstract: ObjectiveTo assess the effects of food supplementation on improving working memory and additional measures including cerebral blood flow in children at risk of undernutrition.DesignRandomized controlled trial.Setting10 villages in Guinea-Bissau.Participants1059 children aged 15 months to 7 years; children younger than 4 were the primary population.InterventionsSupervised isocaloric servings (≈1300 kJ, five mornings each week, 23 weeks) of a new food supplement (NEWSUP, high in plant polyphenols and omega 3 fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 109 publications
(266 reference statements)
6
34
0
1
Order By: Relevance
“…The authors concluded that, “daily supplementation with ≥450 mg DHA + EPA per day and an increase in the Omega-3 Index >6% makes it more likely to show efficacy on cognition in children and adolescents.” [ 3 ]. This conclusion is supported by more recent findings: In children both older and younger than 4 years with undernutrition, a food supplement containing 171 mg EPA and 255 mg DHA per day, and many other components, improved brain blood flow, and parameters of complex brain function, like executive function in a 23-week randomized intervention trial [ 69 ]. The latter findings also point towards the positive effects of supplementing with EPA and DHA in children diagnosed to have a deficit by determining a low Omega-3 Index.…”
Section: Children and Adolescentssupporting
confidence: 53%
“…The authors concluded that, “daily supplementation with ≥450 mg DHA + EPA per day and an increase in the Omega-3 Index >6% makes it more likely to show efficacy on cognition in children and adolescents.” [ 3 ]. This conclusion is supported by more recent findings: In children both older and younger than 4 years with undernutrition, a food supplement containing 171 mg EPA and 255 mg DHA per day, and many other components, improved brain blood flow, and parameters of complex brain function, like executive function in a 23-week randomized intervention trial [ 69 ]. The latter findings also point towards the positive effects of supplementing with EPA and DHA in children diagnosed to have a deficit by determining a low Omega-3 Index.…”
Section: Children and Adolescentssupporting
confidence: 53%
“…Moreover, a high-quality breakfast has been related to a lower risk of obesity [ 4 ]. Thereby, both a nutrient deficit and obesity have been linked to lower cognitive functioning during childhood [ 8 , 9 , 10 ]. Having a regular breakfast and improving its quality could enhance children’s cognitive performance [ 11 , 12 ] through enhanced episodic and visual memory, attention, and other cognitive skills [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular changes leading to enhanced blood flow have received significant attention as mechanisms explaining brain health impact of polyphenols [ 95 , 109 , 159 ]. Polyphenols have been linked to an enhancement of cerebral blood flow and brain oxygenation in clinical trials [ 81 , 160 , 161 , 162 ]. Again, such vascular effects do not require entry of polyphenols into the CNS.…”
Section: How Can Polyphenols Act On the Brain?mentioning
confidence: 99%